Diagnosis of giant cell arteritis: when should we biopsy the temporal artery?. Issue 3 (April 2016) - Hussain, Omar; McKay, Andrew; Fairburn, Kevin; Doyle, Peter; Orr, Robert
Abstract: Giant cell arteritis (GCA) can be diagnosed histopathologically by biopsy of the temporal artery, and clinically using the 5-point score of the 1990 American College of Rheumatology (ACR) classification. We aimed to find out whether some patients are referred for biopsy unnecessarily. We audited all referrals (n = 100) made to the Department of Oral and Maxillofacial Surgery over 34 months, and used the ACR classification to find out whether patients had had a clinical diagnosis of GCA at referral (ACR score: 3 or more). We then compared them with the result of the biopsy. Of the 100 referred, 98 had a biopsy, and of them, 15 were diagnosed with GCA (2 results were not included). Thirteen of the 15 had already been diagnosed clinically (based on the ACR classification) at referral. Our results gave an ACR specificity of 96% (95% CI: 85% to 99%) but only 20% sensitivity (95% CI: 11% to 32%). There was a linear correlation of high ACR scores with histopathological confirmation. Biopsy is most beneficial when there is a degree of diagnostic uncertainty (ACR: 1 or 2), an atypical presentation, or when steroids may be relatively contraindicated. On the basis of our study, we designed a new referral form for biopsy based on the ACR criteria.